Correction to: P92 chronic arthritis as the only manifestation of FMF in Armenian children - Gayane Khloyan; Gayane Amaryan; Rotraud Saurenmann (BMC, 2017)
Abstract Familial Mediterranean Fever (FMF) is the most common inherited auto inflammatory disease, characterized by recurrent, self-limited attacks of fever and aseptic polyserositis.FMF is widespread in Armenia and there is a higher than expected frequency of FMF-associated arthritis in children. Chronic arthritis can be the first, and sometimes the only manifestation of FMF.